2023
DOI: 10.1101/2023.02.14.23285872
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A digital score of peri-epithelial lymphocytic activity predicts malignant transformation in oral epithelial dysplasia

Abstract: Oral squamous cell carcinoma (OSCC) is amongst the most common cancers worldwide, with more than 377,000 new cases worldwide each year. OSCC prognosis remains poor, related to cancer presentation at a late stage indicating the need for early detection to improve patient prognosis. OSCC is often preceded by a premalignant state known as oral epithelial dysplasia (OED), which is diagnosed and graded using subjective histological criteria leading to variability and prognostic unreliability. In this work, we propo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Yet, despite this, OED lesions are often strongly infiltrated with CD8+ T lymphocytes, that may act to reverse this immunosuppressive microenvironment [42,43]. Recent evidence has suggested a higher density of PELs in cases undergoing malignant transformation [26]. This was further supported by Shephard et al [20], who additionally found a potential association between both PELs and IELs and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, despite this, OED lesions are often strongly infiltrated with CD8+ T lymphocytes, that may act to reverse this immunosuppressive microenvironment [42,43]. Recent evidence has suggested a higher density of PELs in cases undergoing malignant transformation [26]. This was further supported by Shephard et al [20], who additionally found a potential association between both PELs and IELs and malignant transformation.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of OED, our previous work has used deep learning to segment dysplasia [19] and also the oral epithelium into sub-regions: the lower basal layer, the middle epithelial layer, and the superior keratin layer [20,21]. These methods have even been used to predict OED malignant transformation, based on either deep [26] or nuclear features [20,27]. Thus, deep learning tools offer a potential avenue for reducing grading variability while ensuring consistency across sites in informing treatment decisions [28,29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation